2011
DOI: 10.1007/s10735-011-9338-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical assessment of intrinsic and extrinsic markers of hypoxia in reproductive tissue: differential expression of HIF1α and HIF2α in rat oviduct and endometrium

Abstract: Hypoxia is thought to be critical in regulating physiological processes within the female reproductive system, including ovulation, composition of the fluid in the oviductal/uterine lumens and ovarian follicle development. This study examined the localisation of exogenous (pimonidazole) and endogenous [hypoxia inducible factor 1α and 2α (HIF1α, -2α), glucose transporter type 1 (GLUT1) and carbonic anhydrase 9 (CAIX)] hypoxia-related antigens within the oviduct and uterus of the rat reproductive tract. The exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…An IHC staining technique was used to examine the number of positive-stained neurons, including InR, IRS-1, PI3K, p-PI3K, AKT and p-AKT. 14 The paraffin sections were kept in a 56°C oven for 1 h. Then, they were moved into p-xylene1 and p-xylene2 in sequence and stayed there for 20 min. Next, the slices were placed in gradient 100%, 95%, 80% and 70% alcohol for 3-5 min, and then they were placed in distilled water.…”
Section: Ihc Staining and Quantificationmentioning
confidence: 99%
“…An IHC staining technique was used to examine the number of positive-stained neurons, including InR, IRS-1, PI3K, p-PI3K, AKT and p-AKT. 14 The paraffin sections were kept in a 56°C oven for 1 h. Then, they were moved into p-xylene1 and p-xylene2 in sequence and stayed there for 20 min. Next, the slices were placed in gradient 100%, 95%, 80% and 70% alcohol for 3-5 min, and then they were placed in distilled water.…”
Section: Ihc Staining and Quantificationmentioning
confidence: 99%
“…[4][5][6] Hypoxia inducible factor 1a (HIF-1a) and HIF-2a are known to be stabilized at different oxygen levels and to have different temporal responses 7 and are expressed in human and rat endometrium. 8,9 Expression of HIF-1a mRNA was observed in eutopic endometrium of women with endometriosis 10 but not in endometriotic tissue, 11 while no data about HIF-2a expression in endometriotic lesions are referred.…”
Section: Introductionmentioning
confidence: 99%
“…In very early studies, the low O 2 concentration status of the oviductal lumen was examined using oxygen probe recordings during the menstrual or oestrous cycle stages of monkeys, hamsters and rabbits (Fischer & Bavister, 1993;Mastroianni & Jones, 1965). In addition, Gillies et al have also confirmed that mucosal regions of the rat oviduct frequently experience severe hypoxia and that there are compartment-specific variations in the expression of endogenous hypoxia-related antigens, including the HIF isoforms (Gillies, Robinson, McPhail, Carter, & Murray, 2011). Most recently, He et al (2020) found that higher mRNA levels of HIF-1α and HIF-2α occur in the oviduct and anterior pituitary compared with the hypothalamus, ovary and uterus in yak, and both of these are higher in these organs of yak than in cattle.…”
Section: Discussionmentioning
confidence: 99%